Extracts and Fractions with antifungal potential for the treatment of hair disorders (Research, Society and Development, 2022)
Medicinal plants are used with several therapeutic applications, with hair disorders. Among the symptoms caused by these diseases, it is pertinent to emphasize the psychic damages such as loss of self-esteem and physical symptoms such as itching and burning. The present study aims to highlight the beneficial effect of medicinal plants against the symptoms caused by hair disorders. This is an integrative literature review using the Pubmed, Science direct and Google Scholar platforms and as descriptors “phytochemical”, “animal”, “seborrheic dermatitis”, “plant”, “anti-inflammatory extracts”, “antifungal” in English, crossed using the Boolean operators “AND” or “OR”. The selection of works took place after reading the title and abstract, with publication date between the years 2012-2022, excluding review studies, duplicate articles and thematic leakage. After extracting the data, 23 studies were selected that proved the effectiveness of plants on hair disorders, performing antifungal action (especially on fungi of the Malassezia spp. and Trichophyton spp.) and antioxidant due to the presence of phytochemical components such as flavonoids, phenolics, tannins, terpenoids, among others. It is noteworthy that most of these plants are processed using the maceration technique to obtain their extracts. Therefore, the bioactive compounds of these plants can be used for the development of pharmaceutical products with the purpose of expanding the therapeutic options on the market and optimizing the quality of life of patients, making it essential to encourage scientific research that discusses safety, efficacy and toxicity from the use of these metabolites.